New term - Cox, Pamela; Enid, Blyton (London : Hodder children books, 2019)
Darrell has left, and Felicity is head of the third form. What a lot she has had to deal with - June and new girl Freddie playing tricks continually, the sickly Bonnie shadowing her, and the stuck-up Amy, who has a strange family secret
Keywords: English - Teenage Fiction book